Canadian Normative Data for Minimal Assessment of Cognitive Function in Multiple Sclerosis. (7th July 2017) - Walker, Lisa A.S.; Marino, David; Berard, Jason A.; Feinstein, Anthony; Morrow, Sarah A.; Cousineau, Denis
Abstract: Objective: The Minimal Assessment of Cognitive Function in Multiple Sclerosis (MACFIMS) is a consensus-based collection of neuropsychological tests that evaluate cognitive functioning in individuals with multiple sclerosis (MS). The tests are typically scored using each respective published test manual, leaving the examiner to make interpretations from norms derived from different American populations. Given demographic differences, this may lead to misinterpretation of findings in Canadians. Our goal was to establish both discrete and regression-based normative data for the MACFIMS based on a largely co-normed Canadian population to allow for improved psychometric interpretation. Methods: MACFIMS data sets were aggregated from across three different Canadian cities (Ottawa, Toronto, and London), yielding a total of 330 healthy control participants from four different studies evaluating cognition in individuals with MS. Given the variety of contributing studies, there was variability in terms of the number of participants completing each measure. Results: Both age-based discrete normative data and demographically adjusted (sex, age, and education) regression-based formulae were established. The demographic variables varied in their contribution to each MACFIMS test in the regression models, predicting 0 to 18% of the variance. Conclusions: Provision of these regression-based formulae will allow for more accurate interpretation of Canadian-derived MACFIMS scores by allowing clinicians to correct for all relevant demographic variables simultaneously, leading to improved clinical decision making for individuals with multiple sclerosis. RÉSUMÉ: Données normatives canadiennes pour le Minimal Assessment of Cognitive Function in Multiple Sclerosis . Objectif : Le Minimal Assessment of Cognitive Function in Multiple Sclerosis (MACFIMS) est un ensemble de tests neuropsychologiques, basé sur un consensus, qui évaluent la fonction cognitive d'individus atteints de sclérose en plaques (SP). Les tests sont habituellement notés selon les directives contenues dans les manuels publiés pour chacun des tests, laissant l'examinateur en faire l'interprétation à partir de normes provenant de différentes populations américaines. Étant donné l'existence de différences démographiques entre différentes populations, cette façon de procéder peut mener à une interprétation erronée des observations chez des sujets canadiens. Le but de notre étude était d'établir des données normatives discrètes ainsi que des données s'appuyant sur une analyse de régression pour le MACFIMS, basées sur une population canadienne de référence, afin d'en améliorer l'interprétation psychométrique. Méthodologie : Des ensembles de données du MACFIMS provenant de trois villes canadiennes (Ottawa, Toronto et London) ont été regroupés, soit au total les données de 330 sujets témoins en bonne santé qui avaient participé à 4 études différentes évaluant la fonction cognitive d'individus atteints de SP. Étant donné la diversité des études, le nombre de participants qui avaient complété chaque mesure pouvait varier. Résultats : Nous avons établi des formules basées sur des données normatives discrètes, selon l'âge, et sur des données ajustées au point de vue démographique (le sexe, l'âge et le niveau de scolarité) à l'analyse de régression. La contribution des variables démographiques à chaque test du MACFIMS variait dans les modèles de régression, prédisant de 0 à 18% de la variance. Conclusions : Des formules basées sur l'analyse de régression permettront une interprétation plus juste des scores canadiens au MACFIMS parce que les cliniciens pourront corriger simultanément les données pour toutes les variables démographiques pertinentes, ce qui entraînera une amélioration des décisions cliniques concernant les patients atteints de MS.